Intraoperative Electrocochleography in Subjects Affected by Vestibular Schwannoma and Ménière's Disease: Comparison of Results. Issue 3 (20th September 2021) - Trecca, Eleonora M. C.; Adunka, Oliver F.; Hiss, Meghan M.; Mattingly, Jameson K.; Moberly, Aaron C.; Dodson, Edward E.; Cassano, Michele; Prevedello, Daniel M.; Riggs, William J.
Abstract : Objectives: Histologic reports of temporal bones of ears with vestibular schwannomas (VSs) have indicated findings of endolymphatic hydrops (ELH) in some cases. The main goal of this investigation was to test ears with VSs to determine if they exhibit electrophysiological characteristics similar to those of ears expected to experience ELH. Design: Fifty-three subjects with surgically confirmed VS aged ≥18 and with normal middle ear status were included in this study. In addition, a second group of adult subjects (n = 24) undergoing labyrinthectomy (n = 6) or endolymphatic sac decompression and shunt (ELS) placement (n = 18) for poorly controlled vestibular symptoms associated with Meniere's disease (MD) participated in this research. Intraoperative electrocochleography (ECochG) from the round window was performed using tone burst stimuli. Audiometric testing and word recognition scores (WRS) were performed preoperatively. ECochG amplitudes, cochlear microphonic/auditory nerve neurophonic (ANN) in the form of the "ongoing" response and summation potential, were analyzed and compared between the two groups of subjects. In addition, to evaluate any effect of auditory nerve function, the auditory nerve score was calculated for each subject. Pure-tone averages were obtained using the average air conduction thresholds at 0.5, 1, and 2 kHz while WRS was assessed using Northwestern University Auditory Test No. 6 word lists. Results: In the VS group the average pure-tone averages and WRS were 59.6 dB HL and 44.8%, respectively, while in the MD group they were 52.3 dB HL and 73.8%. ECochG findings in both groups revealed a reduced trend in amplitude of the ongoing response with increased stimulus frequency. The summation potential amplitudes of subjects with VS were found to be less negative than the MD subjects for nearly all test frequencies. Finally, the VS group exhibited poorer amounts of auditory nerve function compared to the MD group. Conclusions: The current findings suggest cochlear pathology (e.g., hair cell loss) in both groups but do not support the hypothesis that VSs cause ELH.